2005
DOI: 10.1111/j.1442-2018.2005.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Role stress in nurses: Review of related factors and strategies for moving forward

Abstract: The aim of this paper was to review the literature on factors related to role stress in nurses, and present strategies for addressing this issue based on the findings of this review while considering potential areas for development and research. Computerized databases were searched as well as hand searching of articles in order to conduct this review. This review identified multiple factors related to the experience of role stress in nurses. Role stress, in particular, work overload, has been reported as one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
149
1
13

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(172 citation statements)
references
References 54 publications
9
149
1
13
Order By: Relevance
“…Stress is intrinsic to nursing and a highly demanding job with poor support, rapidly changing circumstances, shortage of resources and staff, and dealing with death and dying all contribute (Chang et al, 2005). Nursing is emotionally demanding and this interactive stress contributes to the daily stress of nurses (Mann & Cowburn, 2005).…”
Section: Stressmentioning
confidence: 99%
See 3 more Smart Citations
“…Stress is intrinsic to nursing and a highly demanding job with poor support, rapidly changing circumstances, shortage of resources and staff, and dealing with death and dying all contribute (Chang et al, 2005). Nursing is emotionally demanding and this interactive stress contributes to the daily stress of nurses (Mann & Cowburn, 2005).…”
Section: Stressmentioning
confidence: 99%
“…Environmental factors compound these intrinsic factors and these include difficult patients and their families, relationships with physicians and low institutional commitment to nursing (Chang et al, 2005). In addition to the daily stresses of nursing, nurses are required to undertake continuing professional development (Hogston, 1995) and part-time education (Timmins & Nicholl, 2005).…”
Section: Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis of the literature relating positive and negative affectivity to job-related attitudes found that p = −0.17 based on a k of 18 with N = 5327 between positive affectivity and turnover intentions and that p = 0.28 based on a k of 35 with N = 8671 between negative affectivity and turnover intentions. 15 Chang et al 16 noted that work demands are related to turnover in nurses.…”
Section: Psychological Antecedents Of Absenteeism and Turnovermentioning
confidence: 99%